Inhibition of ferroptosis in inflammatory macrophages alleviates intestinal injury in neonatal necrotizing enterocolitis - Leiting Shen; Jiayu Chen; Jinfa Tou (Cell Death Discovery)
Abstract Neonatal necrotizing enterocolitis (NEC) is a severe gut disease primarily affecting preterm infants, driven significantly by inflammatory macrophages. This study combined bioinformatics (single-cell/tissue RNA sequencing) and experiments to identify key macrophage changes in NEC. Analysis revealed substantial macrophage infiltration in NEC tissues. These macrophages were highly inflammatory and strongly linked to cell death pathways (ferroptosis, pyroptosis, apoptosis), with scores significantly higher than controls and correlating with inflammation. In vitro, LPS-stimulated inflammatory macrophages showed elevated ferroptosis, evidenced by cell rupture, death, increased ACSL4, decreased GPX4, iron overload, lipid peroxidation, and heightened cytokine release. Critically, the ferroptosis inhibitor Ferrostatin-1 (Fer-1) reversed these effects. While LPS alone didn’t kill intestinal epithelial cells, supernatant from LPS-stimulated macrophages significantly increased intestinal epithelial cell death. Fer-1 inhibition of macrophage ferroptosis prevented this epithelial damage. In vivo, a mouse NEC model (induced by hypersomolar feeding, hypoxia, cold) displayed macrophage infiltration, inflammation, and elevated ferroptosis markers. Intraperitoneal Fer-1 administration improved intestinal injury in NEC mice. This study demonstrates that macrophage ferroptosis is a critical driver of NEC inflammation and tissue damage. Inhibiting ferroptosis with Fer-1 effectively reduces both macrophage death and subsequent intestinal epithelial injury, mitigating NEC progression. These findings highlight macrophage ferroptosis as a key therapeutic target for NEC, offering a foundation for new treatment strategies.